Aspectos que influyen en la reconstrucción del proyecto de vida en mujeres que tuvieron un embarazo no planificado durante la adolescencia - Cipagauta Martínez, Laura Alejandra; Rojas Mahecha, Yurany Mayerly (Universidad Antonio Nariño, 2023)
The present investigation was carried out with the objective of analyzing the aspects that influence the elaboration of a life project in women who had an unplanned pregnancy during adolescence. Due to the above, this study was designed under the qualitative approach of a historical hermeneutic type, through a methodology of descriptive scope that would allow identifying the particularities of this population group in said stage of its life cycle.